2012
DOI: 10.1093/hmg/dds207
|View full text |Cite
|
Sign up to set email alerts
|

Signaling defects in iPSC-derived fragile X premutation neurons

Abstract: Fragile X-associated tremor/ataxia syndrome (FXTAS) is a leading monogenic neurodegenerative disorder affecting premutation carriers of the fragile X (FMR1) gene. To investigate the underlying cellular neuropathology, we produced induced pluripotent stem cell-derived neurons from isogenic subclones of primary fibroblasts of a female premutation carrier, with each subclone bearing exclusively either the normal or the expanded (premutation) form of the FMR1 gene as the active allele. We show that neurons harbori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 37 publications
6
99
0
1
Order By: Relevance
“…The recent advances in the use of iPSCs derived from human cells enable the testing of therapeutic strategies Bin a dish^ [225]. Early studies in FXS patient-derived iPSCs suggest that some FXS-associated defects are replicated in these cells [226][227][228], although the classic phenotypes reported in the mouse model, for example exaggerated protein synthesis and altered dendritic spine morphology, have yet to be examined in FXS iPSC-derived neurons. In the future, it will be important to identify robust phenotypes in human iPSCderived neurons from FXS that are suitable to test or screen for therapeutic drugs.…”
Section: Challenges and Future Outlook For Preclinical Studiesmentioning
confidence: 99%
“…The recent advances in the use of iPSCs derived from human cells enable the testing of therapeutic strategies Bin a dish^ [225]. Early studies in FXS patient-derived iPSCs suggest that some FXS-associated defects are replicated in these cells [226][227][228], although the classic phenotypes reported in the mouse model, for example exaggerated protein synthesis and altered dendritic spine morphology, have yet to be examined in FXS iPSC-derived neurons. In the future, it will be important to identify robust phenotypes in human iPSCderived neurons from FXS that are suitable to test or screen for therapeutic drugs.…”
Section: Challenges and Future Outlook For Preclinical Studiesmentioning
confidence: 99%
“…Although most image processing algorithms are used to analyse small stacks of in vitro recordings, 3D dendritic spine analysis has also been carried out in tissue slice cultures 87 and in vivo recordings 107 . Tracking the changes in dendritic spine density and morphology in living animals would not only allow real-time monitoring of the acute effects of drug treatments, but also enable direct correlation of neuronal connectivity parameters with cognitive and behavioural characteristics.Calcium imaging is a valuable tool in the emerging field of iPSC technology to characterize iPSC-derived neurons and to detect phenotypes in patient-derived cultures [108][109][110][111] . Although calcium imaging studies are mostly performed on monocultures, a direct extension of such experiments would be to shift to the co-cultivation of differentially labelled neuronal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Highlighting its importance to neurodevelopment, lines that demonstrated reduced FRM1 expression resulted in aberrant neuronal differentiation [60]. Another study generated iPSC from FXS premutation individuals (carrying 55-200 CGG repeats), who do not display with classical FXS but suffer from neurodegenerative fragile X-associated tremor/ataxia syndrome [61,62]. Interestingly, neurons derived from these iPSCs revealed reduced neurite length, fewer synaptic puncta, reduced synaptic protein levels, and increased calcium stransients [61].…”
Section: Fxsmentioning
confidence: 99%
“…Another study generated iPSC from FXS premutation individuals (carrying 55-200 CGG repeats), who do not display with classical FXS but suffer from neurodegenerative fragile X-associated tremor/ataxia syndrome [61,62]. Interestingly, neurons derived from these iPSCs revealed reduced neurite length, fewer synaptic puncta, reduced synaptic protein levels, and increased calcium stransients [61]. A recent report showed that forebrain neurons derived from iPSCs from patients with FXS also showed reduced neurite outgrowth [63].…”
Section: Fxsmentioning
confidence: 99%